THE ELECTION OF HEAD OF VILLAGE IN THE PERSPECTIVE OF SYSTEM (A Case Study in the Election of Head of Neglasari Village of 2015) - suwaryo, utang; saefulrahman, iyep (Advances in Social Sciences Research Journal, 2017)
THE ELECTION OF HEAD OF VILLAGE IN THE PERSPECTIVE OF SYSTEM (A Case Study in the Election of Head of Neglasari Village of 2015) Utang Suwaryo Department of Government Science Padjadjaran University Bandung, Indonesia Iyep Saefulrahman Department of Government Science Padjadjaran University Bandung, Indonesia Abstract As a law community unit, village has power to manage and arrange its own affairs, among others, elects its leader called head of village. In the perspective of system, the election of head of village is built and moved by several sub-systems. The linkage between the sub-systems is interesting to be studied since any change in one sub-system will affect other sub-systems and the whole system. The study is more interesting since in the case of head of Neglasari village, the village tradition is still prevailed. The research is conducted to analyze the linkage between sub-systems and the work of village tradition in the election of head of Neglasari Village in 2015. Due to the purpose, the research approach used is qualitative research. Data is collected though interview, documentation and observation. Research result shows that in the election of head of Neglasari Village the sub-systems could work and support each other. It can be seen from the election that in accordance with state regulation thus the electoral process as well as resolution of any post-election disputes are worked well. Village tradition that is still ongoing gives color and meaning in the election of head of Neglasari Village in 2015. Therefore, the state needs to give a chance to the village tradition to work along with the state regulation. Keywords: Village, election of head of village, perspective of system